Determination of the second step microstructure for superhydrophobic surfaces. (17th December 2012) - Zhang, Hongyun; Li, Wen; Zhang, Xiaokai; Miao, Fahong; Li, Taohai; Liu, Haihua
Abstract : A selection of suitable microstructures is critical to fabrication and properties of superhydrophobic surfaces (SHS). In this study, we introduce a three‐dimensional droplet model to thermodynamically analyze the superhydrophobic properties for the purpose of determining the second step of a two‐step microstructure suitable for the SHS based on the common models within the reach of the existing macro‐machining technology. It is found that a sinusoidal microstructure is the most suitable, followed by a cone frustum and a prism in the composite wetting state, as well as the transition from hydrophilic to hydrophobic depends basically on the solid fraction rather than non‐determinative surface microscopic topography. The predictions of the model are found in quite good agreement with the experimental observations. This study will facilitate fabrication of the SHS on how to select the suitable morphology. Copyright © 2012 John Wiley & Sons, Ltd.